INFLUENCE OF STYLE OF COMMUNICATION AND SERVICEON CUSTOMER SATISFACTIONAT 74,945.14 SPBU SANDANA TOLI-TOLI - Mirayanti, Mirayanti; Fiansi, Fiansi; Marlina, Marlina; Syamsiar, Syamsiar (Universitas Muhammadiyah Palu, 2020)
The formulation of the problem of this study is whether the communication style affects customer satisfaction, whether the service influences customer satisfaction, and whether the communication style and service simultaneously affect customer satisfaction. From the results of the research conducted, it is known that the variable communication style has a negative effect on the satisfaction variable while the variable has a positive effect on the satisfaction variable, which means that there is an influence between the style of communication and customer satisfaction service at SPBU 74.945.14 Sandana Tolitoli